2014
DOI: 10.1007/s12011-014-0004-x
|View full text |Cite
|
Sign up to set email alerts
|

Source of Copper May Have Regressive Effects on Serum Cholesterol and Urea Nitrogen Among Male Fattening Lambs

Abstract: An experiment was conducted to determine the effect of dietary copper (Cu) on mineral profile, hematological parameters, and lipid metabolism in lambs. Eighteen Zandi male lambs (approximately 3 months of age; 17.53±1.6 kg of body weight) were housed in individual pens and were assigned randomly to one of three treatments. Treatments consisted of (1) control (no supplemental Cu), (2) 10 mg Cu/kg dry matter (DM) from copper sulfate (CuS), and (3) 10 mg Cu/kg DM from Cu proteinate (CuP). The Cu concentration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…In the current study, although serum glucose concentrations were not significantly different among calves fed Cu, Zn and Cu plus Zn supplemented rations vs. control (Table 4), their levels were maintained within the normal physiological ranges reviewed in bovine (Hussein et al, 2013). The results are in keeping with some studies working on cattle (Sobhanirad and Naserian, 2012) and sheep (Hosienpour et al, 2014 andJafarpour et al, 2015). Data illustrated in Table (4) showed a decrease (P<0.05) in serum cholesterol concentrations concomitant with an increase in serum HDL with no significant changes in serum triglycerides for calves fed Cu-supplemented ration vs. control.…”
Section: Serum Metabolic Indicessupporting
confidence: 91%
See 2 more Smart Citations
“…In the current study, although serum glucose concentrations were not significantly different among calves fed Cu, Zn and Cu plus Zn supplemented rations vs. control (Table 4), their levels were maintained within the normal physiological ranges reviewed in bovine (Hussein et al, 2013). The results are in keeping with some studies working on cattle (Sobhanirad and Naserian, 2012) and sheep (Hosienpour et al, 2014 andJafarpour et al, 2015). Data illustrated in Table (4) showed a decrease (P<0.05) in serum cholesterol concentrations concomitant with an increase in serum HDL with no significant changes in serum triglycerides for calves fed Cu-supplemented ration vs. control.…”
Section: Serum Metabolic Indicessupporting
confidence: 91%
“…The decrease in serum cholesterol concentrations with dietary supplemental Cu was also detected in young Holstein bulls (Fagari-Nobijari et al, 2013). Similar responses of these lipid parameters were also noticed with dietary supplemental Cu in male fattening lambs diet (Hosienpour et al, 2014) and finishing steers (Engle et al, 2000). These results may be emphasized that dietary supplemental Cu, at physiological concentrations, can alter plasma lipid metabolism in ruminants (Engle, 2011).…”
Section: Serum Metabolic Indicessupporting
confidence: 69%
See 1 more Smart Citation
“…The leukocyte count has been used as a measure of immune function in birds [ 32 ]. Hosienpour et al [ 33 ] reported that the supplementation of organic minerals did not affect the hematological parameters of lamb. In contrast, previous research reported that supplementation of organic trace minerals increased RBV parameters and hematological response in animals [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cu level was observed maximum in 10 ppm nano Cu supplemented heifers followed by nanoCu 5 and inCu 10 groups. Similarly, increase in plasma Cu concentration in goats (Mondal et al 2017, Shen et al 2020, lambs (Hosienpour et al 2014) and growing heifers (Vaswani et al 2018) was reported on supplementation of Cu (irrespective of organic or inorganic form). On the contrary, a study on dairy cows reported no effect on plasma Cu levels by supplementation of different Cu sources (Sinclair et al 2013).…”
Section: Resultsmentioning
confidence: 85%